Medico-legal borders and the shaping of health services for Afghans in Iran: physical, social, bureaucratic, and public health conditions of care. (2016) - Bisaillon, Laura; Gooshki, Ehsan Shamsi; Briskman, Linda
We report findings from an interdisciplinary scoping exercise carried out in Tehran and Qom, Iran, in August 2014. Our analysis is organised within the four themes of physical, social, bureaucratic, and public health conditions of care, and this work connects with and contributes to what is known about the social conditions of Afghans in Iran. Through this exploratory exercise, we aimed to generate new understandings about issues facing Afghans in healthcare settings in Iran from their perspectives and those of other actors in Iran. This project emerged from concerns about prejudicial treatment of Afghans in clinical settings. We argue and illustrate that an ethics of care approach provides a conceptually and contextually relevant way to develop understandings about and to transform contexts of care. We conclude by anticipating next steps in our research process by building on insights and knowledge produced through this scoping exercise and the tentative analysis that it proffered.